Studying the Efficiency Dependence of CR-39 Detector on the Chamber Height (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
The response of CR-39 plastic detector was computed practically taking into account the most significant parameter of chamber height that effect on efficiency of CR-39. The aim of this project is to calculate the sensitivity of a CR-39 detector in a diffusion chamber for radon measurements using various chamber heights like, (10, 15, 20, 25 and 30) cm. The obtained results revealed that the CR-39 detector's response for the chamber height of (10) cm is about 2 or 3 times higher than that of (15, 20, 25 and 30) cm, this is due to at the small height the concentrations of thoron (220Rn) will be mixing with the concentration of 222Rn.